Evaluation of Phytochemicals and Antibacterial Activity of Indigenous Medicinal plants: Amomum subulatum Roxb. (F.), Astilbe rivularis Buch.-Ham. ex D.Don (R.) and Swertia chirayita (Roxb.) H. Karst (L.) of Dhankuta, Eastern Nepal - Bajimpak, Sanjib; Parajuli, Sanju; Rai, Tujin (Himalayan Journal of Science and Technology, 2024)
This research evaluated the phytochemical composition and antibacterial activity of commonly available indigenous medicinal plant species of Dhankuta, Eastern Nepal. Different plant parts: fruit of Amomum subulatum, rhizome of Astilbe rivularis, and leaves of Swertia Chirayita were used to prepare methanol extracts and the total phenolic and flavonoid content was determined by the Folin-Ciocalteu reagent and Aluminium Chloride method respectively. The antibacterial activity was determined by agar well diffusion assay using bacterial strains, i.e. two gram-negative: Escherichia coli and Salmonella typhi; two gram-positive bacteria: Staphylococcus aureus and Bacillus subtilis. Qualitative phytochemical screening revealed that all three plants contain phenols, flavonoids, tannins, and saponins compounds widely recognized for their antibacterial properties. Steroids were detected in both A. subulatum and A. rivularis, while coumarins were present in A. subulatum and S. chirayita. Terpenoids were identified in A. rivularis and S. chirayita, but absent in A. subulatum. Notably, S. chirayita exhibited the greatest phytochemical diversity, with the presence of alkaloids and glycosides, which were not found in the other two species. The methanolic plant extracts are reported to have 51.11 ± 8.53, 243.70 ± 7.40, 898.02 ± 11.31 (mg GAE/g of extract) of total phenolic content and 157.21 ± 0.99, 590.71 ± 1.51, 869.32 ± 1.14 (mg QE/g of extract) of total flavonoid content of Amomum subulatum (F.), Astilbe rivularis (R.), and Swertia chirayita (L.) respectively. The zone of inhibition ranged from 7 mm to 13.33 mm. Among the three plant extracts, S. chirayita showed the highest, A. rivularis showed the lowest, and A. subulatum showed an intermediate zone of inhibition compared to others in all concentrations (50, 100, and 200 mg/ml). The plant species showed potential antibacterial properties due to the higher availability of the phytochemicals.